The Moderating Role of Innovation Capability in the Relationship Between Corporate Social Responsibility and MSME Performance: A Case Study of PT Arutmin Indonesia Site Asamasam - Rininda, Bella Puspita; Rizka, Nor Rahma; Amelia, Noor; Suasri, Eni; Yakin, Nurul; Ade, M. Syahwal (Yayasan Riset dan Pengembangan Intelektual, 2025)
Micro, Small, and Medium Enterprises (MSMEs) strategically support the national economy. However, they still face various limitations, particularly regarding capital, technological access, and competitiveness. The company's Corporate Social Responsibility (CSR) program is believed to boost the capacity building of MSMEs, but its effectiveness depends on internal factors of the recipients, including their innovation capabilities. This study aims to analyse the role of innovation capability in moderating the influence of CSR on the performance of PT Arutmin Indonesia Site Asamasam fostered MSMEs. The research method uses a quantitative approach with a survey technique through questionnaires distributed to mentored MSME actors. Data analysis was conducted using Partial Least Squares (PLS) regression with the assistance of SmartPLS software. The research findings indicate that CSR has a positive but non-significant effect on MSME performance. Conversely, innovation capability was proven to dominate in improving MSME performance through product development, quality improvement, and business process efficiency. However, innovation capability has not been proven to strengthen the relationship between CSR and MSME performance. This finding confirms that the performance of MSMEs is more determined by internal innovation capacity than by external support through CSR programs alone.